Growth challenges of food processing small-sized enterprises - Yordanov, Danail (2015)
Small-sized food processing enterprises are a vital part of the manufacturing sector of Bulgaria. From their startup, all through the transition period and financial crises, until today, these enterprises have originated, grown, and struggled through many challenges. The purpose of the study is to identify, describe, and analyze the growth challenges and their impact on small-sized enterprises in food processing that have opened and are operating in Bulgaria. Two cases of small, family-run, microenterprizes, from the food processing subsector enterprises, located in the Severoiztochen (North-Eastern) region of Bulgaria were selected for a comparative case study. The biggest challenge for the growth of a small enterprise is the integration of many responsibilities. In small food processing companies, they do not have a different workforce for marketing, operations management, human resources, financial management, and networking. It is done by the same people who started it. The need for finding a proper balance and playing many roles at once makes it very difficult. This requires constant learning, insight, and flexibility. The difficulties cannot be categorized as ‘more or less critical’. Rather they can be grouped into two subcategories: ‘potentially manageable’ and ‘potentially unmanageable’. Growth challenges are correlated and will be considered in their complexities. Case companies are impacted by challenges, both positive and negative. The positive takeaway is that they have been valuable vehicles of managerial learning along the pathway to growth; and the negative is that they have contributed seriously to stalling the rate of growth. Small-sized food processing enterprises, to a large extent, replicate the patterns in other sectors. However, some growth challenges they face are unique; such as those related to food safety. Failure to provide safe food products could translate into discontinuation of the business.